2015
DOI: 10.1002/anie.201506727
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Molybdenum Carbide Nanoparticles Composited with Carbon as a Highly Active Hydrogen‐Evolution Electrocatalyst

Abstract: The replacement of platinum with non-precious-metal electrocatalysts with high efficiency and superior stability for the hydrogen-evolution reaction (HER) remains a great challenge. Herein, we report the one-step synthesis of uniform, ultrafine molybdenum carbide (Mo2C) nanoparticles (NPs) within a carbon matrix from inexpensive starting materials (dicyanamide and ammonium molybdate). The optimized catalyst consisting of Mo2C NPs with sizes lower than 3 nm encapsulated by ultrathin graphene shells (ca. 1-3 lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
265
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(282 citation statements)
references
References 46 publications
17
265
0
Order By: Relevance
“…Besides, the electrochemical impedance spectroscopy images (Supplementary Fig. 15) showed that the Co@NC has a biggest semicircle radius, indicative of a slightly higher charge-transfer impedance than of S-1 (8.53 Ω), of S-2 (8.55 Ω), of S-3 (8.58 Ω), of S-4, of S-5 (8.53 Ω) and of S-6 (8.47 Ω) (refs 51, 52). Therefore, alloying Co with small amount of Ru could lead to a higher charge-transfer rate and more facile catalytic kinetics toward HER.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the electrochemical impedance spectroscopy images (Supplementary Fig. 15) showed that the Co@NC has a biggest semicircle radius, indicative of a slightly higher charge-transfer impedance than of S-1 (8.53 Ω), of S-2 (8.55 Ω), of S-3 (8.58 Ω), of S-4, of S-5 (8.53 Ω) and of S-6 (8.47 Ω) (refs 51, 52). Therefore, alloying Co with small amount of Ru could lead to a higher charge-transfer rate and more facile catalytic kinetics toward HER.…”
Section: Resultsmentioning
confidence: 99%
“…[36] However, further, it was demonstrated that the intrinsic HER activity of Mo 2 C is usually limited by their large density of empty d-orbitals on the Mo, which restricts the desorption of adsorbed H (H ads ) to generate H 2 . [43] However, nitrogen-doping (N-doping) often intermixes into carbon matrix rather than intercalating into Mo 2 C active sites, [16,[44][45][46][47][48] and thus how to construct a controllable N-doping into Mo 2 C activation site still remains a great challenge. [43] However, nitrogen-doping (N-doping) often intermixes into carbon matrix rather than intercalating into Mo 2 C active sites, [16,[44][45][46][47][48] and thus how to construct a controllable N-doping into Mo 2 C activation site still remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] To date, extensive effort has been devoted to exploring advanced techniques for hydrogen production. [5][6][7][8][9][10] Water electrolysis is the simplest electrochemical procedure for producing pure hydrogen and has been one of the most promising processes for a hydrogen-based economy.…”
Section: Introductionmentioning
confidence: 99%